Is the breaststroke arm stroke a "pull" or a "scull"? Part 1 - Maglischo, E. W. (Journal of Swimming Research, 2013)
At the present time swimmers seem to be moving away from using sculling motions in their armstrokes. The trend is back toward the use of drag-dominated propulsion where the hand and arm operate more like a paddle than a foil. While this is true in three of the competitive strokes, a great number of coaches still think breaststroke should be the exception to this trend. They believe swimmers in this stroke should be sculling their hands out and in. In this paper I want to present a case for breaststrokers using drag?dominated propulsion during their armstroke. My rationale for suggesting thiswill be given early in the paper, followed by the presentation of visual and graphic data that support that rationale. In the final section,I will describe how I believe the armstroke should be performed together with a short video showing an Olympic Gold Medalist swimming this way.